2007
DOI: 10.3148/68.1.2007.7
|View full text |Cite
|
Sign up to set email alerts
|

Menu Planning for Childcare Centres: Practices and Needs

Abstract: The results will be relevant to nutritionists in the development of effective resources and training for childcare centre menu planners.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
42
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(46 citation statements)
references
References 10 publications
4
42
0
Order By: Relevance
“…Additionally, we found that high-fibre products such as whole grains and beans/lentils are not consistently included in childcare menus for pre-schoolers. In Nova Scotia, Canada, Romaine and colleagues (30) found that child-care centre menus did not consistently include beans, peas, lentils and other legumes; all items recognized as important sources of Fe, fibre, folate and protein. Given the number of meals Column totals may not add up to the total number of facilities observed (i.e.…”
Section: Food and Beverage Servingsmentioning
confidence: 99%
“…Additionally, we found that high-fibre products such as whole grains and beans/lentils are not consistently included in childcare menus for pre-schoolers. In Nova Scotia, Canada, Romaine and colleagues (30) found that child-care centre menus did not consistently include beans, peas, lentils and other legumes; all items recognized as important sources of Fe, fibre, folate and protein. Given the number of meals Column totals may not add up to the total number of facilities observed (i.e.…”
Section: Food and Beverage Servingsmentioning
confidence: 99%
“…Romaine et al (2007) found that though the majority of individuals in charge of meal planning at childcare centres indicated using Canada's Food Guide ), few received nutrition training specific to young children. Indeed, while research has examined providers' beliefs, relationships with parents, and sources of nutritional information, research is limited in that most studies consider these factors in isolation.…”
Section: Early Childcare Providersmentioning
confidence: 99%
“…Government sources of nutritional information sent to providers have also been found to play a role in the nutritional environment of the childcare setting (Fees, Trost, Bopp, & Dzewaltowski, 2009;Romaine et al, 2007). Romaine et al (2007) found that though the majority of individuals in charge of meal planning at childcare centres indicated using Canada's Food Guide ), few received nutrition training specific to young children.…”
Section: Early Childcare Providersmentioning
confidence: 99%
See 2 more Smart Citations